MATERIAL COMPOSITION AND CONDITIONS OF FORMATION OF LOWER PERMIAN SEDIMENTS IN SOUTHWESTERN PRIMORYE - Malinovsky, A.I. (Vestnik Kamčatskoj regionalʹnoj associacii "Učebno-naučnyj centr". Seriâ: Nauki o Zemle (Online), 2025)
The results of study the material composition of terrigenous rocks of the Early Permian Kazachka formation exposed in the southwestern part of Primorye (Far East of Russia) are considered. The research was carried out with the aim of reconstructing the paleogeodynamic conditions of the formation of sediments, as well as determining the tectonic type and composition of source rocks. Composition of the studied rocks indicate that, in terms of their parameters, they mainly correspond to lithic arenites and arkoses, being petrogenic or «first cycle» rocks that have gone through one cycle of re-deposition of noticeably weathered parent rocks of denudation areas. The paleogeodynamic interpretation of the data obtained indicate that the deposits of the Kazachka formation was formed on an active continental margin, most likely in basins associated with strike-slip dislocations along transform faults. The clastic material came from continental sources areas — cratons and uplifted basement blocks, which were protrusions of the crystalline basement. Acidic igneous rocks and, to a lesser extent basic-medium volcanics and sedimentary rocks enriched with ancient clastic components were eroded.